A kind of extrusion casting high-strength and toughness deformed aluminum alloy and preparation method thereof

By optimizing the composition and structure of aluminum alloy, deeply purifying the aluminum alloy liquid is solved, and the problem of poor plasticity of existing extruded cast aluminum alloys is realized, high-strength and high-plastic extruded cast aluminum alloys are met, and high-strength and tough aluminum alloys are zero Production requirements for components.

CN118668108BActive Publication Date: 2025-02-07GUANGDONG ENG POLYTECHNIC COLLEGE +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410995538.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-24
Publication Date
2025-02-07
Estimated Expiration
2044-07-24

AI Technical Summary

Technical Problem

The existing extruded cast aluminum alloy has poor plasticity and cannot meet the production needs of high-strength aluminum alloy components.

Method used

By optimizing the composition of the aluminum alloy, the structure of the metamorphic aluminum alloy is refined, and the aluminum alloy liquid is deeply purified, thereby improving the casting fluidity, strength and plasticity of the aluminum alloy. Specific ingredients include Mg 0.9-1.1%, Si 0.6-0.8%, Cu 0.2-0.3%, Cr 0.15-0.25%, Mn 0.05-0.15%, Ti 0.01-0.02%, Fe≤0.15%, and the margin is Al and non-existent. Other impurities to avoid.

Benefits of technology

The high strength and high plasticity of extruded cast aluminum alloy are achieved, the tensile strength is greater than 330MPa, the yield strength is greater than 300MPa, and the elongation after break is greater than 12%, while the solid solution aging time is shortened and production costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004960060950000151
    Figure BDA0004960060950000151
Patent Text Reader

Abstract

The invention discloses an extrusion casting high-strength and toughness deformed aluminum alloy and a preparation method thereof, wherein the deformed aluminum alloy is composed of the following components in mass percentage: Mg 0.9-1.1%, Si 0.6-0.8%, Cu 0.2-0.3%, Cr 0.15-0.25%, Mn 0.05-0.15%, Ti 0.01-0.02%, Fe≤0.15%, and the balance is Al and other inevitable impurities. The preparation method comprises the following steps in sequence: heating and melting aluminum ingots, preparing aluminum alloy liquid, online detection and adjustment of components, refining by refining agent spraying, grain refinement treatment, mixed gas spraying refining, extrusion casting, solid solution and aging. The present invention realizes the extrusion casting of the deformed aluminum alloy by optimizing the composition of the deformed aluminum alloy, refining the structure of the aluminum alloy and improving the cleanliness of the aluminum alloy liquid, thereby improving the strength and plasticity of the extrusion cast aluminum alloy. The tensile strength of the extrusion cast deformed aluminum alloy is greater than 330 MPa, the yield strength is greater than 300 MPa, and the elongation after fracture is greater than 12%, thereby meeting the extrusion casting requirements for high-strength, toughness and high-density aluminum alloy structural parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum alloy preparation, and specifically relates to an extrusion casting high-strength and toughness deformed aluminum alloy and a preparation method thereof. Background Art

[0002] Squeeze casting is an advanced molding technology that pours molten metal into a metal mold, and then solidifies and crystallizes the molten metal under the action of extrusion pressure to finally obtain metal parts. Squeeze casting is a molding technology between casting and forging, and has some advantages of both casting and forging. It is widely used in the production of some parts with high requirements for mechanical properties and density, such as aluminum alloy wheels for automobiles and motorcycles, aluminum alloy pistons, cylinder blocks, cylinder heads, transmission boxes, shock absorbers, brakes for engines, aluminum alloy pump bodies for compressors and air compressors, aluminum alloy cranks, steering shafts, frame joints for bicycles, aluminum alloy housings for optical frames, instruments and computers, aluminum alloy pressure cookers, cookware parts, etc. With the development of automobiles, motorcycles, precision instruments and equipment, the mechanical properties of squeeze casting aluminum alloy parts are increasingly required, requiring both high strength and excellent plasticity to meet the design and manufacturing needs of lightweight and improve safety and load-bearing capacity.

[0003] The invention patent with publication number CN1117802364A discloses a high-strength and high-plasticity extrusion casting aluminum alloy and its preparation method. The composition and mass percentage of the aluminum alloy are: Si 6.5-7.5%, Mg 0.25-0.45%, Ti 0.08-0.12%, Sr 0.01-0.03%, Fe ≤ 0.15%, and the rest is Al and impurities. The tensile strength of the extrusion casting aluminum alloy is 306.7-331.1MPa, the yield strength is 272.6-298.4MPa, and the elongation is 8.1-9.6%.

[0004] The invention patent with publication number CN108251714A discloses an extrusion casting high-strength and toughness aluminum alloy and an extrusion casting method thereof. The composition and mass percentage of the aluminum alloy are: Si 9.6-10.4%, Mg 0.9-1.1%, Cu 0.4-0.6%, Ti 0.1-0.2%, Cr 0.05-0.1%, Yb 0.01-0.02%, Te 0.03-0.05%, Fe≤0.15%, and the rest is Al and other inevitable impurity elements. The tensile strength of the extrusion casting aluminum alloy is 351.4-395.1MPa, the yield strength is 303.8-345.2MPa, and the elongation is 6.2-7.2%.

[0005] The invention patent with publication number CN108796317A discloses a semi-solid extrusion cast aluminum alloy suitable for new energy vehicles and a preparation method. The composition and mass percentage of the aluminum alloy are: Si 5-8%, Cu 3.5-4%, Fe 0.4-0.8%, Mg 0-0.5%, and the remaining impurities are controlled below 0.05%, and the balance is Al. The tensile strength of the extrusion cast aluminum alloy is greater than 420MPa, the yield strength is greater than 380MPa, but the elongation is less than 1%.

[0006] The invention patent with publication number CN 107937768 A discloses an extrusion casting aluminum alloy material and a preparation method thereof. The composition and mass percentage of the aluminum alloy are: Si 8-12%, Fe < 0.9, Cu 1-4%, Mn 0.2-0.8%, Mg 0.3-0.8%, Zn < 0.35%, Sn ≤ 0.01%, Cd ≤ 0.01%, the total amount of other impurities does not exceed 0.3%, and the balance is aluminum. The tensile strength of the extrusion casting aluminum alloy is 329.85-354.23MPa, the yield strength is 222.07-224.88MPa, and the elongation is 2.64-2.8%.

[0007] According to the results of literature retrieval and production practice experience, the aluminum alloy used for extrusion casting is mainly cast aluminum silicon alloy. Although cast aluminum silicon alloy has good casting fluidity, the plasticity of cast aluminum silicon alloy is generally poor, making it difficult for extrusion casting aluminum silicon alloy parts to meet the requirements of high-strength and toughness aluminum alloy parts. Deformed aluminum alloy refers to aluminum alloy used for plastic deformation processing such as extrusion, rolling, forging, and stamping. Deformed aluminum alloy usually has excellent plasticity, but the casting fluidity of deformed aluminum alloy is poor, making the existing deformed aluminum alloy unable to meet the production requirements of extrusion casting. Therefore, the existing extrusion casting aluminum alloy and its preparation method still need to be improved and developed. Summary of the invention

[0008] In view of the problems mentioned in the background technology, the purpose of the present invention is to provide an extrusion cast high-strength and toughness deformed aluminum alloy and a preparation method thereof, which improves the casting fluidity, strength and plasticity of the aluminum alloy by optimizing the component composition of the aluminum alloy, refining the structure of the modified aluminum alloy and deeply purifying the aluminum alloy liquid, thereby meeting the production needs of extrusion cast high-strength and toughness aluminum alloy parts.

[0009] The technical solution adopted by the present invention to achieve the above-mentioned purpose is as follows:

[0010] The first aspect of the present invention provides an extrusion casting high-strength and toughness deformed aluminum alloy, characterized in that the aluminum alloy is composed of the following components in mass percentage: Mg 0.9-1.1%, Si 0.6-0.8%, Cu 0.2-0.3%, Cr 0.15-0.25%, Mn 0.05-0.15%, Ti 0.01-0.02%, Fe≤0.15%, and the balance is Al and other inevitable impurities, the individual content of other impurities is ≤0.05%, and the total content of other impurities is ≤0.15%.

[0011] Existing extrusion casting mainly uses cast aluminum silicon alloy. Although aluminum silicon alloy has good casting fluidity and is easy to cast, the strength of aluminum silicon alloy is generally low and the plasticity is poor, which cannot meet the extrusion casting requirements of high-strength and tough aluminum alloy parts. In order to solve the problems and shortcomings of existing cast aluminum silicon alloys, the present invention provides a deformed aluminum alloy for extrusion casting, wherein Mg and Cu are the main strengthening elements of the aluminum alloy. Mg and Cu can not only enhance the strength of the aluminum alloy through solid solution strengthening, but also Mg can further enhance the strength of the aluminum alloy by aging precipitation of Mg2Si phase with Si. Cu can also further enhance the strength of the aluminum alloy by aging precipitation of CuAl2 phase. The higher the content of Mg and Cu, the higher the strength of the aluminum alloy, but too high the content of Mg and Cu will also cause the plasticity of the aluminum alloy to decrease. In order to obtain an aluminum alloy with both high strength and high plasticity, as a preferred embodiment, the content of Mg is 0.9-1.1% and the content of Cu is 0.2-0.3%.

[0012] The Si element in the aluminum alloy can not only enhance the casting fluidity, but also further enhance the strength of the aluminum alloy by precipitating the Mg2Si phase through aging with Mg. The higher the Si content, the better the casting fluidity of the aluminum alloy and the higher the strength. However, too high Si content will also cause the plasticity of the aluminum alloy to decrease. In order to obtain an aluminum alloy with good casting fluidity, high strength and high plasticity, as a preferred embodiment, the Si content is 0.6-0.8%.

[0013] Cr and Mn can enhance the strength of aluminum alloy by forming MnAl6 and CrAl7 dispersed particles, and also refine the grains, inhibit grain growth, and increase the recrystallization temperature. The higher the content of Cr and Mn, the higher the strength of the aluminum alloy. However, too high a content of Cr and Mn will also cause the plasticity of the aluminum alloy to decrease. Preferably, the content of Cr is 0.15-0.25%, and the content of Mn is 0.05-0.15%.

[0014] The Ti element is added to the aluminum alloy in the form of aluminum-titanium alloy. Its main function is to refine the grain structure of the aluminum alloy and improve the casting fluidity and uniformity of the aluminum alloy. The Ti content cannot be too low, otherwise the grain refinement effect will not be obvious. The Ti content does not need to be too high. Too high a Ti content will not enhance the grain refinement effect, but will increase the production cost. Preferably, the Ti content is 0.01-0.02%.

[0015] Fe is an inevitable impurity element in aluminum alloys. It usually exists in the form of coarse needle-shaped or flaky Fe-rich phases such as FeAl3 and Fe2SiAl9 in aluminum alloys, which will split the aluminum matrix of the aluminum alloy, destroy the organizational continuity of the aluminum alloy, cause local stress concentration in the aluminum alloy, become the crack source and crack extension direction of the aluminum alloy fracture, and reduce the strength and plasticity of the aluminum alloy. Therefore, the content of impurity element Fe must be strictly controlled. As a preferred embodiment, the content of Fe is ≤0.15%.

[0016] A second aspect of the present invention provides a method for preparing a high-strength and toughness deformed aluminum alloy by extrusion casting, characterized in that it comprises the following steps in sequence:

[0017] Step 1: Heat and melt the aluminum ingot, and raise the temperature of the aluminum liquid to 740-760℃;

[0018] Step 2: adding magnesium source, silicon source, copper source, chromium source and manganese source into the aluminum liquid, stirring and melting into aluminum alloy liquid;

[0019] Step 3: Online detection and adjustment of the composition of aluminum alloy liquid;

[0020] Step 4: using argon gas and powder refining agent to spray and refine the aluminum alloy liquid;

[0021] Step 5: Add refiner to refine and modify the aluminum alloy liquid;

[0022] Step 6: Using mixed gas to spray and refine the aluminum alloy liquid;

[0023] Step 7: extruding the aluminum alloy liquid into aluminum alloy, and then cooling and solidifying to room temperature;

[0024] Step eight: performing solid solution treatment and aging on the aluminum alloy to obtain the extrusion casting high-strength and toughness deformed aluminum alloy.

[0025] Preferably, in step 1, the aluminum content of the aluminum ingot is ≥ 99.7%. The purity of the aluminum ingot is the basis for ensuring that the aluminum alloy composition meets the requirements. If the purity of the aluminum ingot is low and the content of impurity elements is too high, it will directly affect the purity of the aluminum alloy. The higher the purity of the aluminum ingot, the more conducive it is to obtain a high-purity aluminum alloy and ensure the performance of the aluminum alloy. However, the higher the purity of the aluminum ingot, the higher the price, which will increase the production cost. In order to ensure the purity of the aluminum alloy liquid and reduce the production cost, an aluminum ingot with an aluminum content of 99.7% is preferred.

[0026] Preferably, in step 2, the magnesium source is a magnesium ingot with a magnesium content of ≥99.9%, the silicon source is an aluminum-silicon alloy with a silicon content of 24-26%, the copper source is an aluminum-copper alloy with a copper content of 19-21%, the chromium source is an aluminum-chromium alloy with a chromium content of 9-11%, and the manganese source is an aluminum-manganese alloy with a manganese content of 14-16%. The purity of the magnesium ingot and the alloy will also affect the purity of the aluminum alloy, but too high a purity will also increase the production cost. In order to ensure the purity of the aluminum alloy and reduce the production cost, a magnesium ingot with a magnesium content of 99.9% is preferred.

[0027] Preferably, in step three, the online detection of the composition of the aluminum alloy liquid is to cast the aluminum alloy liquid into an aluminum alloy sample in an aluminum melting furnace, and after turning and flattening, the composition of the aluminum alloy sample is detected on-site on a direct reading spectrometer or a handheld spectrometer. The online adjustment of the composition of the aluminum alloy liquid is to compare the composition of the aluminum alloy sample with the composition requirements of the target aluminum alloy. If the content of an element is lower than the composition requirements of the target aluminum alloy, it is supplemented by adding the element. If the content of an element exceeds the composition requirements of the target aluminum alloy, the aluminum alloy liquid is diluted by adding aluminum ingots until the element content of the aluminum alloy liquid meets the composition requirements of the target aluminum alloy.

[0028] Preferably, in step 4, the purity of the argon gas is ≥99.99%, the amount of the powder refining agent is 0.1-0.2% of the weight of the aluminum alloy liquid, the temperature of the aluminum alloy liquid during the spray refining is 700-720°C, and the spray refining time is 15-20 minutes.

[0029] The spray refining adopts a powder spraying tank and a stainless steel pipe, and uses argon as a carrier to spray the powder refining agent into the aluminum alloy liquid, so that the powder refining agent contacts and reacts with the aluminum alloy liquid, and then the inclusions and hydrogen in the aluminum alloy liquid are taken out of the aluminum alloy liquid. The deslagging and dehydrogenation effect of spray refining is related to the purity of argon, the amount of refining agent, the quality of refining agent, the temperature of the aluminum alloy liquid and the spray refining time. The higher the purity of argon, the greater the amount of refining agent, the longer the spray refining time, the better the deslagging and dehydrogenation effect, but the production cost will also increase accordingly. If the temperature of the aluminum alloy liquid is too high or the spray refining time is too long, the oxidation and burning of the aluminum alloy liquid will also increase. After the spray refining is completed, after removing the scum on the surface of the aluminum alloy liquid, a covering agent should be sprinkled on the surface of the aluminum alloy liquid in time to avoid oxidation and burning of the aluminum alloy liquid and hydrogen absorption. After sprinkling the covering agent, the aluminum alloy liquid needs to be left standing for a period of time so that inclusions and bubbles in the aluminum alloy liquid have sufficient time to escape. The standing time of the aluminum alloy liquid is not less than 30 minutes, and preferably the standing time of the aluminum alloy liquid is 30-40 minutes.

[0030] Preferably, in step 4, the powder refining agent consists of the following components in mass percentage: NaCl 35.12%, NaF 19.84%, TiCl 3 16.51%, SrSO 4 10.06%, KPO 3 11.45%, and Na 2 B 4 O 7 7.02%.

[0031] The deslagging and dehydrogenation effect of powder spray refining is closely related to the composition of the powder refining agent. Existing powder refining agents are mainly obtained by crushing and mixing fluoride salts and chloride salts, which leads to low deslagging and dehydrogenation efficiency of powder refining agents, large emission of irritating smoke and single function, which makes it difficult to meet the needs of high-strength and tough aluminum alloys in extrusion casting. In order to improve the deslagging and dehydrogenation effect of powder spray refining, the present invention has developed a high-efficiency and environmentally friendly multifunctional powder refining agent, in which NaCl reacts with aluminum liquid to generate AlCl3 with a boiling point of only 180°C. AlCl3 bubbles escape from aluminum liquid by adsorbing and capturing inclusions and hydrogen during the floating process, thereby playing a role in deslagging and dehydrogenation. The main function of NaF is to destroy the aluminum oxide film by forming molten salt, dissolve inclusions such as aluminum oxide into the molten salt, increase the surface tension between inclusions and aluminum liquid, promote the separation of inclusions such as aluminum oxide from aluminum liquid, and enhance the deslagging function of the powder refining agent. TiCl3 reacts with aluminum liquid to generate AlCl3 bubbles. During the floating process, AlCl3 bubbles absorb and capture inclusions and hydrogen in the aluminum liquid, enhancing the deslagging and dehydrogenating capabilities of the powder refining agent. The Ti element obtained by the reaction enters the aluminum liquid, which can further enhance the grain effect on the aluminum alloy and improve the uniformity of the organizational composition of the aluminum alloy. SrSO4 reacts with aluminum liquid to generate SO2 bubbles. During the floating process, SO2 bubbles can absorb and capture inclusions and hydrogen in the aluminum liquid, enhancing the deslagging and dehydrogenating capabilities of the powder refining agent. The Sr element obtained by the reaction enters the aluminum liquid, which can refine the eutectic Si phase in the modified aluminum alloy and improve the strength and plasticity of the aluminum alloy. KPO3 reacts with aluminum liquid to generate P element, which enters the aluminum liquid, and can refine the primary Si phase in the modified aluminum alloy, which can not only improve the strength and plasticity of the aluminum alloy, but also enhance the wear resistance of the aluminum alloy. Na2B4O7 reacts with aluminum liquid to generate B element which enters into aluminum liquid, and can refine the coarse Fe-rich phase in the modified aluminum alloy, eliminate the harm of the coarse Fe-rich phase to the strength and plasticity of the aluminum alloy, and improve the strength and plasticity of the aluminum alloy.

[0032] Preferably, in step 4, the method for preparing the powder refining agent comprises the following steps in sequence:

[0033] Step 1: According to the composition and mass percentage of the powder refining agent, NaCl, NaF, TiCl3, SrSO4, KPO3, and Na2B4O7 with a purity of ≥99.8% are selected as raw materials for batching; Step 2: Add the ingredients into water at a temperature of 70°C and stir to dissolve into an aqueous solution, the mass ratio of water to the ingredients is 1.2, and then heat to 100°C to evaporate the aqueous solution to obtain solid crystals; Step 3: Crush the solid crystals into powder with a particle size of less than 2 mm, and dry and dehydrate the powder at 160°C for 4 hours to obtain the powder refining agent.

[0034] The deslagging and dehydrogenation effects of powder refining agents are closely related to their preparation methods. Existing powder refining agents are usually obtained by directly mixing chloride salts and fluoride salts after mechanical crushing. The components of this powder refining agent exist independently of each other, the melting point of the powder refining agent is high, and there is a lack of synergy between the components, resulting in low deslagging and dehydrogenation efficiency of the refining agent. The present invention breaks through the traditional preparation method and adopts a solution evaporation method to prepare a powder refining agent. Through solution evaporation, the components are re-solidified and recrystallized to form a eutectic with a lower melting point. For example, the melting point of NaCl is usually 801°C, and the melting point of NaF is usually 993°C. When the two form a NaCl·NaF eutectic, the melting point drops to 698°C, thereby greatly reducing the melting point of the powder refining agent, making the powder refining agent easier to dissolve in the aluminum alloy liquid, and playing a synergistic role in deslagging and dehydrogenation, which can significantly enhance the deslagging and dehydrogenation functions of the powder refining agent.

[0035] Preferably, in step five, the refiner is an Al-5Ti-1B alloy rod or an Al-5Ti-0.2C alloy rod, and the amount of the refiner added is 0.2-0.4% of the weight of the aluminum alloy liquid. The purpose of adding the refiner is to refine the α-Al grains and improve the fluidity and uniformity of the aluminum alloy liquid. If the refiner is not added for refinement and modification, coarse dendritic α-Al grains will be formed during the solidification of the aluminum alloy liquid, which will not only reduce the fluidity of the aluminum alloy liquid and increase the difficulty of filling, but also cause component segregation and uneven organization inside the aluminum alloy. The grain refiner can be an Al-5Ti-1B alloy rod or an Al-5Ti-0.2C alloy rod, and the amount added cannot be less than 0.2%, otherwise the grain refinement effect is not obvious. The addition amount does not need to exceed 0.4%, and the addition amount exceeding 0.4% will not significantly increase the grain refinement effect, but will increase the production cost.

[0036] Preferably, in step 6, the amount of the mixed gas is 2-3 cubic meters per ton of aluminum alloy liquid, and the pressure of the mixed gas is 0.3-0.5×10 5 Pa, the temperature of the aluminum alloy liquid during spray refining is 700-720℃, and the spray refining time is 10-15 minutes.

[0037] After powder spray refining, the gas slag content of aluminum alloy liquid has been greatly reduced, but the aluminum alloy liquid still contains gas slag, because the powder refining agent refining process re-introduces inclusions such as chloride salts and fluoride salts. In addition, although the powder refining agent spray refining also has a dehydrogenation effect, the dehydrogenation effect is limited. The reason is that the powder refining agent inevitably contains water, which will also be introduced during the spray refining dehydrogenation, causing the aluminum alloy liquid to absorb hydrogen again, so that the dehydrogenation of the powder refining agent spray refining is always in a dynamic equilibrium process. It is difficult for the powder refining agent spray refining to reduce the hydrogen content of the aluminum alloy liquid to below 0.2ml / 100gAl. Therefore, in order to obtain a highly clean aluminum alloy liquid, refining, dehydrogenation and deslag removal are also necessary.

[0038] The mixed gas injection refining adopts a stainless steel pipe or a degasser to inject the mixed gas into the aluminum alloy liquid, so that the mixed gas forms fine bubbles that contact and react with the aluminum alloy liquid, and the hydrogen and inclusions in the aluminum alloy liquid are brought out of the liquid surface by the floating of the bubbles, so as to achieve the purpose of deep slag removal and hydrogen removal.

[0039] The dehydrogenation and slag removal effect of mixed gas spray refining is related to the amount of mixed gas used, the temperature of the aluminum alloy liquid and the spray refining time. The greater the amount of mixed gas used, the longer the spray refining time, and the better the deslagging and dehydrogenation effect of the spray refining, but the production cost will also increase accordingly. If the temperature of the aluminum alloy liquid is too high or the spray refining time is too long, the oxidation and burning of the aluminum alloy liquid will also increase. After the spray refining is completed and the scum on the surface of the aluminum alloy liquid is removed, a covering agent should be sprinkled on the surface of the aluminum alloy liquid in time to avoid oxidation and burning of the aluminum alloy liquid and hydrogen absorption. After sprinkling the covering agent, the aluminum alloy liquid needs to be left to stand for a period of time so that the bubbles in the aluminum alloy liquid have sufficient time to escape. The standing time of the aluminum alloy liquid cannot be less than 20 minutes. Preferably, the standing time of the aluminum alloy liquid is 20-30 minutes.

[0040] Preferably, in step six, the mixed gas is composed of argon gas with a purity of ≥99.99%, sulfur hexafluoride and carbon monoxide, the volume percentage of sulfur hexafluoride in the mixed gas is 9-11%, and the volume percentage of carbon monoxide is 3-5%.

[0041] In the existing gas injection refining technology, inert gas nitrogen or argon, or a mixture of inert gas and chlorine, is usually injected into the aluminum alloy liquid. The relative molecular mass of nitrogen is 28.01 and the density is 1.25kg / m 3 The relative molecular mass of argon is 39.94 and the density is 1.78 kg / m 3 The relative molecular mass of chlorine is 70.91 and the density is 3.21kg / m 3. Due to the small relative molecular mass and low density of nitrogen, argon and chlorine, the bubbles float up faster in the aluminum alloy liquid, and the contact time between the bubbles and the aluminum alloy liquid is shorter, which limits the time for the bubbles to capture and adsorb hydrogen and inclusions, greatly affecting the dehydrogenation and deslagging effect of gas injection refining. In addition, although the relative density of chlorine is relatively large, chlorine is a toxic gas with a strong pungent odor, which will not only seriously corrode the smelting furnace and smelting tools, but also cause serious environmental pollution.

[0042] Aiming at the problems and shortcomings of the existing gas injection refining technology, in order to improve the dehydrogenation and slag removal effect of gas injection refining, the present invention injects a mixed gas consisting of argon with a purity of ≥99.99%, sulfur hexafluoride with a purity of ≥99.99% and carbon monoxide with a purity of ≥99.99% into the aluminum alloy liquid, wherein sulfur hexafluoride is a high-density and high-stability gas with a relative molecular mass of 146.05 and a density of 6.5kg / m 3 , and sulfur hexafluoride is non-toxic, non-flammable and non-corrosive. Adding 9-11% by volume of sulfur hexafluoride to the mixed gas can significantly slow down the floating speed of bubbles in the aluminum alloy liquid, increase the contact time between the bubbles and the aluminum alloy liquid, and enable the bubbles to capture and absorb more hydrogen and inclusions, thereby improving the dehydrogenation and deslagging effect of gas injection refining. Adding 3-5% by volume of carbon monoxide to the mixed gas is to allow carbon monoxide to capture oxygen in the aluminum alloy liquid to form carbon dioxide, prevent oxygen from forming an aluminum oxide film on the surface of the bubble again with aluminum, enhance the ability of the bubbles to capture and absorb hydrogen and inclusions, and improve the deslagging and dehydrogenation effect of gas injection refining. Through mixed gas injection refining, the hydrogen content of the aluminum alloy liquid can be reduced to below 0.14ml / 100gAl, and the inclusion content can be reduced to 0.09mm 2 / kgAl or less, thereby greatly improving the cleanliness of the aluminum alloy liquid.

[0043] Preferably, in step seven, the mold preheating temperature during extrusion casting is 300-330°C, the pouring temperature of the aluminum alloy liquid is 740-760°C, the extrusion pressure ratio is 150-170MPa, the filling speed is 220-230mm / s, and the holding time is 18-20 seconds.

[0044] In order to obtain a complete and dense extrusion casting aluminum alloy, the extrusion casting process must be reasonably set. Since the casting fluidity of the deformed aluminum alloy is worse than that of the aluminum silicon alloy, the extrusion casting molding process of the deformed aluminum alloy cannot refer to the extrusion casting molding process of the traditional aluminum silicon alloy, and must be re-optimized. The inventor has conducted a large number of experimental studies on the extrusion casting molding process of the deformed aluminum alloy. The results show that the preheating temperature of the extrusion casting mold cannot be lower than 300°C, the pouring temperature of the aluminum alloy liquid cannot be lower than 740°C, the extrusion pressure ratio cannot be lower than 150MPa, and the filling speed cannot be lower than 220 mm / s, otherwise it will cause the extrusion casting aluminum alloy to be incompletely filled or cold shut defects on the surface. The preheating temperature of the mold should not be too high, and the casting temperature should not be too high, otherwise it will increase the cooling time and reduce production efficiency. The extrusion pressure ratio cannot be higher than 170MPa, and the filling speed cannot be higher than 230 mm / s, otherwise it will cause the aluminum alloy liquid to splash and entrain in the mold cavity, resulting in defects such as pores and looseness inside the aluminum alloy.

[0045] Preferably, in step eight, the solution treatment is to heat the aluminum alloy at 540-550°C for 30-60 minutes, and then cool the aluminum alloy to room temperature in water. The aging treatment is to heat the aluminum alloy after the solution treatment at 180-190°C for 90-120 minutes, and then cool it to room temperature in the furnace.

[0046] Solution and aging are important means to improve the mechanical properties of aluminum alloys. The solution temperature of existing aluminum alloys is usually 520-530℃. Due to the low solution temperature, it is not only difficult to obtain a supersaturated solid solution, but also leads to a long solution time and low production efficiency. Similarly, the aging temperature of existing aluminum alloys is usually 150-160℃. Due to the low aging temperature, the aging time is long and the production efficiency is low. Through a large number of experimental explorations and studies, the inventors found that by increasing the solution temperature of aluminum alloys to 540-550℃, a supersaturated solid solution can be obtained by heating and keeping warm for 30-60 minutes. Similarly, by increasing the aging temperature of aluminum alloys to 180-190℃, it only takes 90-120 minutes of heating and keeping warm to obtain high-strength and high-plasticity extrusion casting aluminum alloys. At the same time, the heating and keeping warm time of solution aging can be greatly shortened, thereby reducing production costs and improving production efficiency.

[0047] Compared with the prior art, the present invention has the following beneficial effects: by optimizing the composition of aluminum alloy, refining the structure of modified aluminum alloy and improving the cleanliness of aluminum alloy liquid, the present invention realizes the extrusion casting of deformed aluminum alloy, greatly improves the strength and plasticity of extrusion casting aluminum alloy, and the tensile strength of extrusion casting deformed aluminum alloy is greater than 330MPa, the yield strength is greater than 300MPa, and the elongation after fracture is greater than 12%. In addition, the present invention also shortens the solution aging time of extrusion casting deformed aluminum alloy, which is conducive to reducing the production cost of extrusion casting deformed aluminum alloy and improving production efficiency DETAILED DESCRIPTION

[0048] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] Example 1

[0050] The extrusion casting high-strength and toughness deformed aluminum alloy is composed of the following components in mass percentage: Mg 0.99%, Si 0.72%, Cu 0.26%, Cr 0.19%, Mn 0.11%, Ti 0.015%, Fe ≤ 0.15%, the balance is Al and other inevitable impurities, the individual content of other impurities is ≤ 0.05%, and the total content of other impurities is ≤ 0.15%. The preparation method comprises the following steps in sequence: step 1: heating and melting an aluminum ingot with an aluminum content of 99.7%, and raising the temperature of the aluminum liquid to 750°C; step 2: adding a magnesium ingot with a magnesium content of 99.9%, an aluminum-silicon alloy with a silicon content of 25%, an aluminum-copper alloy with a copper content of 20%, an aluminum-chromium alloy with a chromium content of 10%, and an aluminum-manganese alloy with a manganese content of 15% into the aluminum liquid, stirring and melting into an aluminum alloy liquid; step 3: adjusting the components of the aluminum alloy liquid Online detection and adjustment are performed until the composition of the aluminum alloy liquid meets the composition requirements of the aluminum alloy; Step 4: Use argon with a purity of 99.99% and a powder refining agent of 0.15% by weight of the aluminum alloy liquid to spray and refine the 710°C aluminum alloy liquid for 18 minutes; Step 5: Add 0.3% of the weight of the aluminum alloy liquid Al-5Ti-1B alloy rod for refinement and modification; Step 6: Use a mixed gas composed of argon with a purity of 99.99%, sulfur hexafluoride and carbon monoxide to spray and refine the 710°C aluminum alloy liquid for 13 minutes, the amount of the mixed gas is 2.5 cubic meters / ton of aluminum alloy liquid, and the pressure of the mixed gas is 0.4×10 5Pa, the volume percentage of sulfur hexafluoride in the mixed gas is 10%, and the volume percentage of carbon monoxide is 4%; step seven: under the conditions of mold preheating temperature of 315°C, pouring temperature of aluminum alloy liquid of 750°C, extrusion pressure ratio of 160MPa, filling speed of 225mm / s, and holding time of 19 seconds, the aluminum alloy liquid is extruded and cast into aluminum alloy; step eight: solutionizing the aluminum alloy at 545°C for 45 minutes, and then aging the aluminum alloy at 185°C for 100 minutes to obtain the extrusion casting high-strength and toughness deformed aluminum alloy.

[0051] Example 2

[0052] The extrusion casting high-strength and toughness deformed aluminum alloy is composed of the following components in mass percentage: Mg 0.9%, Si 0.8%, Cu 0.2%, Cr 0.25%, Mn 0.05%, Ti 0.02%, Fe ≤ 0.15%, the balance is Al and other inevitable impurities, the individual content of other impurities is ≤ 0.05%, and the total content of other impurities is ≤ 0.15%. The preparation method comprises the following steps in sequence: Step 1: heating and melting an aluminum ingot with an aluminum content of 99.7%, and raising the temperature of the aluminum liquid to 760°C; Step 2: adding a magnesium ingot with a magnesium content of 99.9%, an aluminum-silicon alloy with a silicon content of 24%, an aluminum-copper alloy with a copper content of 21%, an aluminum-chromium alloy with a chromium content of 11%, and an aluminum-manganese alloy with a manganese content of 14% into the aluminum liquid, stirring and melting into an aluminum alloy liquid; Step 3: adjusting the components of the aluminum alloy liquid Online detection and adjustment are performed until the composition of the aluminum alloy liquid meets the composition requirements of the aluminum alloy; Step 4: Use argon with a purity of 99.99% and a powder refining agent of 0.2% by weight of the aluminum alloy liquid to spray and refine the 700°C aluminum alloy liquid for 20 minutes; Step 5: Add 0.4% of the weight of the aluminum alloy liquid Al-5Ti-1B alloy rod for refinement and modification; Step 6: Use a mixed gas composed of argon with a purity of 99.99%, sulfur hexafluoride and carbon monoxide to spray and refine the 720°C aluminum alloy liquid for 10 minutes, the amount of the mixed gas is 3 cubic meters / ton of aluminum alloy liquid, and the pressure of the mixed gas is 0.5×10 5 Pa, the volume percentage of sulfur hexafluoride in the mixed gas is 11%, and the volume percentage of carbon monoxide is 3%; step seven: under the conditions of mold preheating temperature of 330°C, pouring temperature of aluminum alloy liquid of 740°C, extrusion pressure ratio of 170MPa, filling speed of 220mm / s, and holding time of 18 seconds, the aluminum alloy liquid is extruded and cast into aluminum alloy; step eight: solutionizing the aluminum alloy at 550°C for 30 minutes, and then aging the aluminum alloy at 180°C for 120 minutes to obtain the extrusion casting high-strength and toughness deformed aluminum alloy.

[0053] Example 3

[0054] The extrusion casting high-strength and toughness deformed aluminum alloy is composed of the following components in mass percentage: Mg 1.1%, Si 0.6%, Cu 0.3%, Cr 0.15%, Mn 0.15%, Ti 0.01%, Fe ≤ 0.15%, the balance is Al and other inevitable impurities, the individual content of other impurities is ≤ 0.05%, and the total content of other impurities is ≤ 0.15%. The preparation method comprises the following steps in sequence: step 1: heating and melting an aluminum ingot with an aluminum content of 99.7%, and raising the temperature of the aluminum liquid to 740°C; step 2: adding a magnesium ingot with a magnesium content of 99.9%, an aluminum-silicon alloy with a silicon content of 26%, an aluminum-copper alloy with a copper content of 19%, an aluminum-chromium alloy with a chromium content of 9%, and an aluminum-manganese alloy with a manganese content of 16% into the aluminum liquid, stirring and melting into an aluminum alloy liquid; step 3: adjusting the components of the aluminum alloy liquid Online detection and adjustment until the composition of the aluminum alloy liquid meets the composition requirements of the aluminum alloy; Step 4: Use argon with a purity of 99.99% and a powder refining agent of 0.1% by weight of the aluminum alloy liquid to spray and refine the aluminum alloy liquid at 720°C for 15 minutes; Step 5: Add 0.2% of the weight of the aluminum alloy liquid Al-5Ti-0.2C alloy rod for refinement and modification; Step 6: Use a mixed gas composed of argon with a purity of 99.99%, sulfur hexafluoride and carbon monoxide to spray and refine the aluminum alloy liquid at 700°C for 15 minutes, the amount of the mixed gas is 2 cubic meters / ton of aluminum alloy liquid, and the pressure of the mixed gas is 0.3×10 5 Pa, the volume percentage of sulfur hexafluoride in the mixed gas is 9%, and the volume percentage of carbon monoxide is 5%; step seven: under the conditions of mold preheating temperature of 300°C, pouring temperature of aluminum alloy liquid of 760°C, extrusion pressure ratio of 150MPa, filling speed of 230mm / s, and holding time of 20 seconds, the aluminum alloy liquid is extruded and cast into aluminum alloy; step eight: solutionizing the aluminum alloy at 540°C for 60 minutes, and then aging the aluminum alloy at 190°C for 90 minutes to obtain the extrusion casting high-strength and toughness deformed aluminum alloy.

[0055] Example 4

[0056] The powder refining agent described in step 4 of Example 1-3 is composed of the following components in mass percentage: NaCl35.12%, NaF 19.84%, TiCl3 16.51%, SrSO4 10.06%, KPO3 11.45%, and Na2B4O77.02%. The preparation method of the powder refining agent comprises the following steps in sequence: (1) According to the composition and mass percentage of the powder refining agent, NaCl, NaF, TiCl3, SrSO4, KPO3, and Na2B4O7 with a purity of 99.8% are selected as raw materials for batching; (2) the ingredients are added into water at a temperature of 70°C and stirred to dissolve into an aqueous solution, the mass ratio of water to the ingredients being 1.2, and then the aqueous solution is heated to 100°C to evaporate to obtain solid crystals; (3) the solid crystals are crushed into powder with a particle size of less than 2 mm, and the powder is dried and dehydrated at 160°C for 4 hours to obtain the powder refining agent.

[0057] Example 5

[0058] The composition, mass percentage and preparation method of the extrusion casting deformed aluminum alloy in this embodiment are the same as those in Example 1, except that the powder refining agent used in step 4 is a conventional powder refining agent available on the market, and the powder refining agent is composed of the following components in mass percentage: NaCl 36.13%, KCl 15.42%, CaF2 16.84%, NaF 19.24%, C2Cl6 12.37%, and the powder refining agent is obtained by directly crushing and mixing the raw materials after drying and dehydration.

[0059] Example 6

[0060] The composition, mass percentage and preparation method of the extrusion cast deformed aluminum alloy in this embodiment are the same as those in Example 1, except that in step five, no mixed gas is used to spray and refine the aluminum alloy liquid, but argon gas with a purity of 99.99% is used to spray and refine the aluminum alloy liquid.

[0061] Verification Example

[0062] The hydrogen content and slag content of the aluminum alloy liquid of Examples 1-3 and Examples 5-6 before extrusion casting were tested on site using a HDA-V hydrogen meter and an Analyze PoDFA slag meter. The results are shown in Table 1. As can be seen from Table 1, the hydrogen content of the aluminum alloy liquid of Examples 1-3 is less than 0.14 ml / 100 gAl, and the slag content is less than 0.09 mm 2 / kgAl. In Example 5, the conventional powder refining agent on the market was used for spray refining, and in Example 6, the mixed gas was not used for spray refining, resulting in a relatively high gas-slag content in the aluminum alloy liquid. By comparison, it can be seen that the technical solution of the present invention can significantly reduce the gas-slag content of the aluminum alloy liquid before squeeze casting and improve the cleanliness of the squeeze cast aluminum alloy.

[0063] Table 1 Hydrogen content and slag content of aluminum alloy liquid

[0064] Hydrogen content / (ml / 100gAl) <![CDATA[Sludge content / (mm 2 / kg Al)]]> Example 1 0.109 0.071 Example 2 0.137 0.087 Example 3 0.128 0.076 Example 5 0.191 0.182 Example 6 0.217 0.159

[0065] Samples were taken from the extrusion casting deformed aluminum alloys obtained in Examples 1-3 and 5-6 to test the tensile mechanical properties and Brinell hardness of the deformed aluminum alloys, and the results are shown in Table 2. As can be seen from Table 2, the tensile strength of the deformed aluminum alloys in Examples 1-3 is greater than 330 MPa, the yield strength is greater than 300 MPa, and the elongation after fracture is greater than 12%. However, the tensile strength of the deformed aluminum alloys in Examples 5 and 6 is less than 310 MPa, the yield strength is less than 280 MPa, and the elongation after fracture is less than 10%. By comparison, it can be seen that the strength and plasticity of the extrusion casting deformed aluminum alloy can be significantly improved by the technical solution of the present invention.

[0066] Table 2 Tensile mechanical properties of squeeze casting deformed aluminum alloy

[0067]

Claims

1. A method for preparing a high-strength and toughness deformed aluminum alloy by extrusion casting, characterized in that: The deformed aluminum alloy is composed of the following components in mass percentage: Mg 0.9-1.1%, Si 0.6-0.8%, Cu 0.2-0.3%, Cr 0.15-0.25%, Mn 0.05-0.15%, Ti 0.01-0.02%, Fe≤0.15%, the balance is Al and other inevitable impurities, the content of each other impurity is ≤0.05%, and the total content of other impurities is ≤0.15%; the preparation method comprises the following steps in sequence: Step 1: Heat and melt the aluminum ingot, and raise the temperature of the aluminum liquid to 740-760℃; Step 2: adding magnesium source, silicon source, copper source, chromium source and manganese source into the aluminum liquid, stirring and melting into aluminum alloy liquid; Step 3: Online detection and adjustment of the composition of aluminum alloy liquid; Step 4: using argon gas and powder refining agent to spray and refine the aluminum alloy liquid; Step 5: Add refiner to refine and modify the aluminum alloy liquid; Step 6: Using mixed gas to spray and refine the aluminum alloy liquid; Step 7: extruding the aluminum alloy liquid into aluminum alloy, and then cooling and solidifying to room temperature; Step 8: performing solid solution treatment and aging on the aluminum alloy to obtain the extrusion casting high-strength and toughness deformed aluminum alloy; The powder refining agent in step 4 is composed of the following components in mass percentage: NaCl 35.12%, NaF 19.84%, TiCl3 16.51%, SrSO4 10.06%, KPO3 11.45%, and Na2B4O7 7.02%. The preparation method comprises the following steps in sequence: (1) According to the composition and mass percentage of the powder refining agent, NaCl, NaF, TiCl3, SrSO4, KPO3, and Na2B4O7 with a purity of ≥99.8% are selected as raw materials for batching; (2) the ingredients are added into water at a temperature of 70°C and stirred to dissolve into an aqueous solution, the mass ratio of water to ingredients being 1.2, and then the aqueous solution is evaporated at 100°C to obtain a solid crystal; (3) the solid crystal is crushed into a powder with a particle size of less than 2 mm, and the powder is dried and dehydrated at 160°C for 4 hours to obtain the powder refining agent; The mixed gas in step 6 is composed of argon gas with a purity of ≥99.99%, sulfur hexafluoride and carbon monoxide, the volume percentage of sulfur hexafluoride in the mixed gas is 9-11%, and the volume percentage of carbon monoxide is 3-5%; In step 7, the mold preheating temperature during extrusion casting is 300-330° C., the pouring temperature of the aluminum alloy liquid is 740-760° C., the extrusion pressure ratio is 150-170 MPa, the filling speed is 220-230 mm / s, and the holding time is 18-20 seconds.

2. The method for preparing a high-strength and toughness deformed aluminum alloy by extrusion casting according to claim 1, characterized in that: The aluminum content of the aluminum ingot in step one is ≥99.7%, the magnesium source in step two is a magnesium ingot with a magnesium content ≥99.9%, the silicon source is an aluminum-silicon alloy with a silicon content of 24-26%, the copper source is an aluminum-copper alloy with a copper content of 19-21%, the chromium source is an aluminum-chromium alloy with a chromium content of 9-11%, and the manganese source is an aluminum-manganese alloy with a manganese content of 14-16%.

3. The method for preparing a high-strength and toughness deformed aluminum alloy by extrusion casting according to claim 1, characterized in that: The purity of the argon gas in step 4 is ≥99.99%, the amount of the powder refining agent is 0.1-0.2% of the weight of the aluminum alloy liquid, the temperature of the aluminum alloy liquid during the spray refining is 700-720°C, and the spray refining time is 15-20 minutes.

4. The method for preparing a high-strength and toughness deformed aluminum alloy by extrusion casting according to claim 1, characterized in that: The refiner in step 5 is an Al-5Ti-1B alloy rod or an Al-5Ti-0.2C alloy rod, and the amount of the refiner added is 0.2-0.4% of the weight of the aluminum alloy liquid.

5. The method for preparing a high-strength and toughness deformed aluminum alloy by extrusion casting according to claim 1, characterized in that: The amount of the mixed gas in step 6 is 2-3 cubic meters per ton of aluminum alloy liquid, and the pressure of the mixed gas is 0.3-0.5×10 5 Pa, the temperature of the aluminum alloy liquid during spray refining is 700-720℃, and the spray refining time is 10-15 minutes.

6. The method for preparing a high-strength and toughness deformed aluminum alloy by extrusion casting according to claim 1, characterized in that: The solution treatment in step eight is to heat the aluminum alloy at 540-550°C for 30-60 minutes, and then cool the aluminum alloy to room temperature water; the aging treatment is to heat the aluminum alloy after the solution treatment at 180-190°C for 90-120 minutes, and then cool it to room temperature with the furnace.

Citation Information

Patent Citations

  • Extrusion casting aluminum alloy material and preparation method thereof

    CN107937768A

  • Squeeze casting high strength and toughness aluminum alloy and squeeze casting method thereof

    CN108251714A

  • Semi-solid state extrusion casting aluminum alloy for new energy automobile and preparation method thereof

    CN108796317A

  • High-strength easy-to-extrude aluminum alloy and profile extrusion method thereof

    CN115852217A

  • Aluminum profile for battery box body of new energy automobile and manufacturing method of aluminum profile

    CN118127386A